Preparation method and application of CS / PPy-based composite fiber aerogel
The preparation of CS/PPy-based composite fiber aerogels has solved the problems of high cost and severe energy loss in photothermal conversion materials, achieving low-cost and efficient water purification and removal of various pollutants, and possessing excellent flexibility and reusability.
Patent Information
- Application Number
- CN202411448885.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-17
AI Technical Summary
Existing photothermal conversion materials are costly, complex to prepare, and suffer significant energy loss, making it difficult to efficiently remove various pollutants from water.
A CS/PPy-based composite fiber aerogel was used to prepare a continuous fiber structure aerogel matrix by electrospinning technology, and a PPy coating was deposited in situ on it. Combined with glutaraldehyde stabilization treatment, a composite material with low thermal conductivity and high flexibility was formed.
It achieves a low-cost and simple preparation process, improves photothermal conversion efficiency and the removal capacity of various pollutants in water, reduces heat loss, and has excellent flexibility and reusability.
Smart Images

Figure CN119287553A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of novel composite materials, and in particular relates to a preparation method and application of a CS / PPy-based composite fiber aerogel. Background Art
[0002] Water shortage around the world has become an urgent problem to be solved. Currently, the commonly used treatment methods mainly include chemical precipitation, adsorption, photocatalytic degradation, membrane separation and desalination distillation. In actual wastewater, the composition of pollutants is quite complex. It is of great significance to develop new materials that can remove multiple pollutants and achieve water system purification at the same time.
[0003] Photothermal conversion materials can collect solar energy and convert it into thermal energy. By changing the environmental parameters of the water system, pure water can be extracted from it and various pollutants can be removed. Therefore, they are considered to be a low-cost, safe, renewable and environmentally friendly water purification technology. However, most photothermal conversion materials are expensive and have complex preparation processes, often involving complex treatment processes such as supercritical drying or freeze drying. In addition, the photothermal conversion process usually requires continuous contact with the water body. Under the action of diffusion, heat will continue to flow to the non-evaporating part of the water body, causing a large amount of energy loss and low conversion efficiency. Therefore, there is an urgent need to develop new composite photothermal conversion materials that are simple, efficient, and have low thermal conductivity to achieve water purification and the removal of various pollutants in water.
[0004] Aerogel materials are one of the ideal materials for photothermal conversion and water purification due to their unique microstructure and physical properties. The high porosity of aerogels gives them low thermal conductivity, which can effectively reduce energy loss. However, aerogels are mostly composed of discontinuous solid networks, have poor mechanical properties, and are not easy to recycle. Summary of the invention
[0005] The purpose of the embodiments of the present invention is to provide a preparation method and application of CS / PPy-based composite fiber aerogel, aiming to solve the problems raised in the above background technology.
[0006] The embodiment of the present invention is implemented as follows: a method for preparing a CS / PPy-based composite fiber aerogel, wherein the CS / PPy-based composite fiber aerogel comprises a CS / FeCl3 fiber aerogel matrix and a PPy coating having photothermal conversion performance, and the method comprises the following steps:
[0007] Step 1, CS and FeCl3 are dissolved in trifluoroacetic acid / dichloromethane mixed solvent respectively to obtain CS and FeCl3 solutions, wherein the volume ratio of trifluoroacetic acid to dichloromethane in the mixed solvent is 4:1. The FeCl3 solution is added dropwise to the CS solution to prepare a uniform spinning solution, wherein the volume ratio of the CS solution to the FeCl3 solution is 3:1 to 5:1;
[0008] Step 2, obtaining a CS / FeCl3 fiber aerogel matrix by electrospinning technology;
[0009] Step 3, adding a certain amount of pyrrole monomer to the bottom of the sealed container, placing the CS / FeCl3 fiber aerogel matrix on the top of the container, heating to make the pyrrole vapor in situ deposit and polymerize PPy on the surface of the matrix fiber, and obtaining the CS / PPy-based composite fiber aerogel;
[0010] Step 4: The obtained CS / PPy-based composite fiber aerogel is placed above the container without moving, a certain amount of glutaraldehyde is added to the bottom of the sealed container and heated to generate glutaraldehyde vapor, so as to stabilize the CS / PPy-based composite fiber aerogel.
[0011] According to a further technical solution, in step 1, the ratio of the mass of CS in the CS solution to the volume of the mixed solvent is 38-57 mg / mL, and the ratio of the mass of FeCl3 in the FeCl3 solution to the volume of the mixed solvent is 30-50 mg / mL.
[0012] According to a further technical solution, in step 2, the electrospinning technical parameters are: voltage of 14-17 kV, distance of 10-15 cm, push speed of 1-4 mL / h, temperature of 19-25° C., humidity of 42-66%, and electrospinning time of 0.5-2 h.
[0013] In a further technical solution, in step 3, the volume of pyrrole is 200-400 μL, and the area of CS / PPy-based composite fiber aerogel is 8-10 cm 2 , thickness is 1 to 2 cm, mass is 10 to 150 mg, reaction temperature is 40 to 60°C, and reaction time is 20 to 24 h.
[0014] According to a further technical solution, in step 4, the volume of glutaraldehyde is 4 to 6 mL, the reaction temperature is 60 to 90° C., and the reaction time is 8 to 12 h.
[0015] Another purpose of an embodiment of the present invention is to provide an application of a CS / PPy-based composite fiber aerogel, based on the CS / PPy-based composite fiber aerogel prepared by the above method, and apply the CS / PPy-based composite fiber aerogel in the field of water purification.
[0016] As a further technical solution, the water purification field specifically includes solar interfacial evaporation, and the removal and collection of pollutants (organic dyes, drugs, heavy metal ions and oil pollutants, etc.) in wastewater.
[0017] The preparation method and application of a CS / PPy-based composite fiber aerogel provided in an embodiment of the present invention have the following beneficial effects:
[0018] (1) An aerogel matrix with a continuous fiber structure is directly prepared by electrospinning technology. The preparation process is simple, and the aerogel matrix has excellent flexibility, which solves the practical application problem of repeated recycling and saves costs;
[0019] (2) CS / PPy-based composite fiber aerogel has low thermal conductivity, which can inhibit heat loss. At the same time, the amino groups on the CS fiber aerogel can undergo hydration, reduce the evaporation enthalpy of water, and increase the solar evaporation rate;
[0020] (3) The fiber structure of CS / PPy-based composite fiber aerogel can perform multiple light refractions, enhance light capture, and improve photothermal conversion efficiency;
[0021] (4) CS / PPy-based composite fiber aerogel has the ability to remove a variety of pollutants in water, combined with efficient photothermal conversion performance, and has a good water purification effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The photos and SEM morphology of fiber aerogels;
[0023] Figure 2 is the infrared spectrum of fiber aerogel;
[0024] Figure 3 This is the infrared thermal imaging image of CS / PPy-based composite fiber aerogel under 1sun irradiation;
[0025] Figure 4 The water mass change-time curve of CS / PPy-based composite fiber aerogel in the solar interface evaporation experiment;
[0026] Figure 5 The evaporation rate, photothermal conversion efficiency and UV-visible absorption spectra before and after evaporation of different organic dye wastewaters;
[0027] Figure 6 The evaporation rate, photothermal conversion efficiency and UV-visible absorption spectra before and after evaporation of different pharmaceutical wastewaters;
[0028] Figure 7 The evaporation rate, photothermal conversion efficiency and the concentration of heavy metal ions before and after evaporation of wastewater with different heavy metal ions;
[0029] Figure 8 is the mass of CS / PPy-based composite fiber aerogel before and after crude oil adsorption under light and without light;
[0030] Fig. 9 Oil-water emulsion separation performance of CS / PPy-based composite fiber aerogel. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0032] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.
[0033] An embodiment of the present invention provides a method for preparing a CS / PPy-based composite fiber aerogel, wherein the CS / PPy-based composite fiber aerogel comprises a CS / FeCl3 fiber aerogel matrix and a PPy coating having photothermal conversion performance, and the method comprises the following steps:
[0034] Step 1, CS and FeCl3 are dissolved in trifluoroacetic acid / dichloromethane mixed solvent respectively to obtain CS and FeCl3 solutions, wherein the volume ratio of trifluoroacetic acid to dichloromethane in the mixed solvent is 4:1. The FeCl3 solution is added dropwise to the CS solution to prepare a uniform spinning solution, wherein the volume ratio of the CS solution to the FeCl3 solution is 3:1 to 5:1;
[0035] Step 2, obtaining a CS / FeCl3 fiber aerogel matrix by electrospinning technology;
[0036] Step 3, adding a certain amount of pyrrole monomer to the bottom of the sealed container, placing the CS / FeCl3 fiber aerogel matrix on the top of the container, heating to make the pyrrole vapor in situ deposit and polymerize PPy on the surface of the matrix fiber, and obtaining the CS / PPy-based composite fiber aerogel;
[0037] Step 4: The obtained CS / PPy-based composite fiber aerogel is placed above the container without moving, a certain amount of glutaraldehyde is added to the bottom of the sealed container and heated to generate glutaraldehyde vapor, so as to stabilize the CS / PPy-based composite fiber aerogel.
[0038] As a preferred embodiment of the present invention, in step 1, the ratio of the mass of CS in the CS solution to the volume of the mixed solvent is 38-57 mg / mL, and the ratio of the mass of FeCl3 in the FeCl3 solution to the volume of the mixed solvent is 30-50 mg / mL.
[0039] As a preferred embodiment of the present invention, in step 2, the electrospinning technical parameters are: voltage of 14-17 kV, distance of 10-15 cm, push speed of 1-4 mL / h, temperature of 19-25°C, humidity of 42-66%, and electrospinning time of 0.5-2 h.
[0040] As a preferred embodiment of the present invention, in step 3, the volume of pyrrole is 200-400 μL, and the area of CS / PPy-based composite fiber aerogel is 8-10 cm 2 , thickness is 1 to 2 cm, mass is 10 to 150 mg, reaction temperature is 40 to 60°C, and reaction time is 20 to 24 h.
[0041] As a preferred embodiment of the present invention, in step 4, the volume of glutaraldehyde is 4-6 mL, the reaction temperature is 60-90° C., and the reaction time is 8-12 h.
[0042] As a preferred embodiment of the present invention, the preparation method is specifically as follows:
[0043] (1) Preparation of CS / FeCl3 fiber aerogel matrix:
[0044] 0.19 g CS was dissolved in 4 mL trifluoroacetic acid / dichloromethane mixed solvent (v / v, 4 / 1) to obtain CS solution, and 0.04 g FeCl3 was dissolved in 1 mL trifluoroacetic acid / dichloromethane mixed solvent (v / v, 4 / 1) to obtain FeCl3 solution. Then, 1 mL FeCl3 solution was added dropwise to 4 mL CS solution to prepare a uniform spinning solution. The spinning solution was electrospun under the conditions of spinning distance 15 cm, voltage 16 kV, propulsion speed 2.0 mL / h, and electrospinning time 1 h to obtain CS / FeCl3 fiber aerogel matrix.
[0045] (2) Preparation of CS / PPy-based composite fiber aerogel:
[0046] Add 400 μL of pyrrole monomer to the bottom of the sealed container. Take an area of 9.62 cm 2 A CS / FeCl3 fiber aerogel matrix with a thickness of 1.5 cm was placed on top of the container and heated at 50°C to generate pyrrole vapor. The temperature was kept for 24 h, and PPy was in situ deposited and polymerized on the surface of the fiber aerogel to obtain a CS / PPy-based composite fiber aerogel, which was recorded as CS / PPy.
[0047] (3) Stabilization treatment of CS / PPy-based composite fiber aerogel:
[0048] The CS / PPy-based composite fiber aerogel was placed on top of the container and kept still. 5 mL of glutaraldehyde was added to the bottom of the sealed container and heated at 75°C to generate glutaraldehyde vapor. The temperature was kept for 10 h to stabilize the CS / PPy-based composite fiber aerogel, which was recorded as CS / PPy / GA.
[0049] Figure 1In the figure, a, c and e are photos of the fiber aerogels in (1)-(3), and b, d and f are SEM morphology images of the fiber aerogels in (1)-(3). The area of the CS / PPy-based composite fiber aerogel in the figure is 9.62 cm 2 , thickness is 1.5cm, density is 9.83mg / cm 3 Microscopically, the CS / PPy-based composite fiber aerogel is composed of continuous fibers with a fiber diameter of 826 nm and a PPy coating thickness of approximately 20 nm.
[0050] Figure 2 The infrared spectra of the fiber aerogels in Examples (1) to (3) are shown in Table 1. The infrared curve of CS / Fe at 3352 cm -1 The broad peaks on the left and right are the stretching vibration peaks of OH and NH, 1529 cm -1 The 840 and 798 cm-1 peaks of CS / PPy are the bending vibration peaks of NH. -1 The plane bending vibration peak of the pyrrole ring appears at the infrared curve of CS / PPy / GA, and the stretching vibration peaks of OH and NH and the bending vibration peaks of NH are enhanced, which proves the in-situ deposition polymerization of PPy. The bending vibration peak of NH disappears on the infrared curve of CS / PPy / GA, and the stretching vibration peaks of OH and NH are also weakened, which proves the cross-linking of glutaraldehyde.
[0051] As a preferred embodiment of the present invention, the solar interface evaporation performance test of CS / PPy-based composite fiber aerogel was carried out:
[0052] 140 mg of CS / PPy-based composite fiber aerogel was adsorbed in water for a sufficient time and then placed under an evaporation device. A solar simulator equipped with an AM1.5G filter was used, and the light intensity was adjusted to 1 sun, with an illumination area of 9.62 cm 2 After irradiation for 2 h, the temperature change was recorded using an infrared thermal imaging device, and the mass change caused by water evaporation was measured using a balance.
[0053] Figure 3 This is an infrared thermal image of the CS / PPy-based composite fiber aerogel under 1sun irradiation. In a dry state, the fiber aerogel can quickly heat up from 24.8°C to 80.4°C within 1 minute. Even in a fully water-wetted state, the aerogel will heat up from 20.6°C to 38.0°C within 15 minutes and remain stable, indicating its excellent photothermal conversion performance.
[0054] Figure 4The water mass change-time curve of CS / PPy-based composite fiber aerogel in the solar interface evaporation experiment. The results show that the curve is linear, indicating that the water evaporation performance of the fiber aerogel is stable. According to calculations, the solar interface water evaporation rate is as high as 2.27kg / m 2 h, the photothermal conversion efficiency exceeds 96%.
[0055] As a preferred embodiment of the present invention, CS / PPy-based composite fiber aerogel is used to purify wastewater containing different organic dyes:
[0056] Wastewater containing different concentrations of organic dyes were prepared: 10 mg / L methyl orange (MO), rhodamine B (RhB) and methyl blue (MB), 100 mg / L MB and 1000 mg / L MB. 140 mg CS / PPy-based composite fiber aerogel was used to adsorb the wastewater and then placed under an evaporation device with a light intensity of 1 sun and a light area of 9.62 cm 2 After irradiation for 4 hours, record the mass change caused by evaporation of wastewater. At the same time, collect the purified wastewater and test its pollutant concentration.
[0057] Figure 5 The evaporation rate, photothermal conversion efficiency and UV-visible absorption spectra of different organic dye wastewater before and after evaporation. The evaporation rate of all dye wastewater exceeds 1.9kg / m 2 h, the photothermal conversion efficiency exceeds 81%. After purification, the characteristic peak of the dye in the UV-visible absorption spectrum completely disappears, and the removal rate is close to 100%, indicating its efficient purification ability of organic dye wastewater.
[0058] As a preferred embodiment of the present invention, CS / PPy-based composite fiber aerogel is used to purify wastewater containing different drugs:
[0059] Wastewater containing different drugs was prepared: amoxicillin (AM), ciprofloxacin (CIP) and tetracycline hydrochloride (TCH), all with a concentration of 100 mg / L. 140 mg of CS / PPy-based composite fiber aerogel was used to adsorb the wastewater and then placed under an evaporation device with a light intensity of 1 sun and a light area of 9.62 cm 2 After irradiation for 4 hours, record the mass change caused by evaporation of wastewater. At the same time, collect the purified wastewater and test its pollutant concentration.
[0060] Figure 6 The evaporation rate, photothermal conversion efficiency and UV-visible absorption spectra of different pharmaceutical wastewater before and after evaporation. The evaporation rate of all pharmaceutical wastewater exceeded 1.88 kg / m 2h, the photothermal conversion efficiency exceeds 80%. After purification, the characteristic peak of the drug in the UV-visible absorption spectrum completely disappears, and the removal rate is close to 100%, indicating its efficient drug wastewater purification ability.
[0061] As a preferred embodiment of the present invention, CS / PPy-based composite fiber aerogel is used to purify wastewater containing different heavy metal ions:
[0062] Wastewater containing different heavy metal ions was prepared: K2Cr2O7, CuSO4 and MnCl2, with a concentration of 5000 mg / L. 140 mg of CS / PPy-based composite fiber aerogel was used to adsorb the wastewater and then placed under an evaporation device with a light intensity of 1 sun and a light area of 9.62 cm 2 After irradiation for 4 hours, record the mass change caused by evaporation of wastewater. At the same time, collect the purified wastewater and test its pollutant concentration.
[0063] Figure 7 The evaporation rate, photothermal conversion efficiency and concentration of heavy metal ions before and after evaporation of wastewater with different heavy metal ions are shown in Figure 1. The rate exceeds 1.92 kg / m 2 h, the photothermal conversion efficiency exceeds 85%. After purification, the concentration of each ion is less than 0.14mg / L, and the removal rate reaches 99.9%, which meets the drinking water standards set by the World Health Organization, indicating its efficient heavy metal ion wastewater purification ability.
[0064] As a preferred embodiment of the present invention, the effect of the photothermal properties of CS / PPy-based composite fiber aerogel on crude oil adsorption was tested:
[0065] 2g crude oil was placed on 50mL water surface to simulate crude oil leakage. 10mg CS / PPy-based composite fiber aerogel was placed on the surface of crude oil. After 10min, the mass changes with and without light were recorded.
[0066] Figure 8 is the mass of CS / PPy-based composite fiber aerogel before and after crude oil adsorption under light and without light. According to calculations, the crude oil adsorption capacity of CS / PPy-based composite fiber aerogel is only 44g / g without light, while under light, its crude oil adsorption capacity increases to 115g / g. This is because the viscosity of crude oil decreases rapidly with the increase of temperature, thereby achieving improved adsorption performance.
[0067] As a preferred embodiment of the present invention, the oil-water emulsion separation performance of the CS / PPy-based composite fiber aerogel was tested:
[0068] Add 0.1 g of Tween 20 to 100 mL of water, then add 1 mL of oil (n-heptane, n-hexane, toluene and petroleum ether) dropwise, and stir for 6 h to form an oil-in-water emulsion. Take 140 mg of CS / PPy-based composite fiber aerogel and place it in a separator. Pour the emulsion into the separator for separation. The effective contact area is 9.62 cm 2 The separation flux and efficiency of the water-in-oil emulsion were recorded. Taking the water-in-hexane emulsion as an example, ethanol was used for washing after separation, dried at room temperature, and then the emulsion was separated again after drying. The cycle stability was tested for 10 consecutive times.
[0069] Fig. 9 The oil-water emulsion separation performance of CS / PPy-based composite fiber aerogel. CS / PPy-based composite fiber aerogel was used to separate n-hexane, n-heptane, toluene, petroleum ether and water, and the separation fluxes were 3178.01, 2987.26, 2659.31 and 2504.13 L / m 2 h, and the separation efficiency is higher than 99%. Taking the water-in-hexane emulsion as an example, even after 10 cycles, the separation flux and efficiency are still 2799.28L / m 2 h and 99.08%, indicating that the CS / PPy-based composite fiber aerogel has good cyclic stability.
[0070] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a CS / PPy-based composite fiber aerogel, characterized in that: The CS / PPy-based composite fiber aerogel comprises a CS / FeCl3 fiber aerogel matrix and a PPy coating having photothermal conversion performance, and the method comprises the following steps: Step 1, CS and FeCl3 are respectively dissolved in a trifluoroacetic acid / dichloromethane mixed solvent to obtain CS and FeCl3 solutions, wherein the volume ratio of trifluoroacetic acid to dichloromethane in the mixed solvent is 4:1; the FeCl3 solution is added dropwise into the CS solution to prepare a uniform spinning solution, wherein the volume ratio of the CS solution to the FeCl3 solution is 3:1 to 5:1; Step 2, obtaining a CS / FeCl3 fiber aerogel matrix by electrospinning technology; Step 3, adding a certain amount of pyrrole monomer to the bottom of the sealed container, placing the CS / FeCl3 fiber aerogel matrix on the top of the container, heating to make the pyrrole vapor in situ deposit and polymerize PPy on the surface of the matrix fiber, and obtaining the CS / PPy-based composite fiber aerogel; Step 4: The obtained CS / PPy-based composite fiber aerogel is placed above the container without moving, a certain amount of glutaraldehyde is added to the bottom of the sealed container and heated to generate glutaraldehyde vapor, so as to stabilize the CS / PPy-based composite fiber aerogel.
2. The method for preparing the CS / PPy-based composite fiber aerogel according to claim 1, characterized in that: In the step 1, the ratio of the mass of CS in the CS solution to the volume of the mixed solvent is 38-57 mg / mL, and the ratio of the mass of FeCl3 in the FeCl3 solution to the volume of the mixed solvent is 30-50 mg / mL.
3. The method for preparing the CS / PPy-based composite fiber aerogel according to claim 2, characterized in that: In step 2, the electrospinning technical parameters are: voltage of 14-17 kV, distance of 10-15 cm, push speed of 1-4 mL / h, temperature of 19-25° C., humidity of 42-66%, and electrospinning time of 0.5-2 h.
4. The method for preparing the CS / PPy-based composite fiber aerogel according to claim 3, characterized in that: In step 3, the volume of pyrrole is 200-400 μL, and the area of CS / PPy-based composite fiber aerogel is 8-10 cm 2 , thickness is 1 to 2 cm, mass is 10 to 150 mg, reaction temperature is 40 to 60°C, and reaction time is 20 to 24 h.
5. The method for preparing the CS / PPy-based composite fiber aerogel according to claim 4, characterized in that: In step 4, the volume of glutaraldehyde is 4 to 6 mL, the reaction temperature is 60 to 90° C., and the reaction time is 8 to 12 h.
6. An application of a CS / PPy-based composite fiber aerogel, wherein the CS / PPy-based composite fiber aerogel is prepared by the method for preparing the CS / PPy-based composite fiber aerogel according to any one of claims 1 to 5, characterized in that: The CS / PPy-based composite fiber aerogel is applied in the field of water purification.
7. The use of the CS / PPy-based composite fiber aerogel according to claim 6, characterized in that: The water purification field specifically includes solar interfacial evaporation, and the removal and collection of organic dyes, drugs, heavy metal ions and oil pollutants in wastewater.
Citation Information
Patent Citations
Preparation method of magnetic chitosan composite with adsorption characteristic
CN108057423A
Aerogel micro powder and preparation method thereof
CN108689412A
Preparation method and application of aerogel-polypyrrole photo-thermal conversion material
CN110734575A
Subtilisin variants with improved perhydrolase activity
US20050281773A1
Janus composite for oil in water separation
US20230212037A1